McLeod gauge calibration calculations - Baier, W. E. (1934)
These calibrations and the diagram were done by W. E. Baier, Research Manager of the California Fruit Growers' Exchange. The McLeod Gauge measures very low pressures of gasses. Its presence in this collection indicates that it was used during the production of Beckman Instruments' early pH meters.
Keywords: Pressure gages; Numerical calculations; Scientific apparatus and instruments--Calibration; Scientific apparatus and instruments